Financial and Economic Analysis Irrigation Area Development Bajayu – Serdang Bedagai - Mahliza Nasution; Dedi Rahmad; Rusyanto Rusyanto (SPECTA Journal of Technology, 2018)
Serdang Bedagai is one of the rice granaries in North Sumatera Province, but its agricultural potential has not been well managed due to lack of water for irrigation, especially in the dry season.With bajayu weir construction, is expected to improve water demand forclean water and irrigation for agricultural processes can be developed and managed bygood.The cost of construction of the dam construction is very large, so it needs to be reviewed if the benefits and income generated are proportional to the costs and losses incurred.The final goal of this research is to conduct financial and economic analysis in the construction of bajayu weir.This study uses financial and economic analysis using Net Present Value (NPV), Internal Rate of Return (IRR), Benefit cost Ratio (BCR) indicators and also analyzes sensitivity due to cost changes.Optimal handling is estimated after 10 years, so within that time the benefit increases linearly until the 13th year and will remain from year 13 to the next.From the calculation of finance development of bajau irrigation area obtained NPV = Rp.1.778.603.070.507,62-, IRR = 27%, BCR = 4.6.And from the economic calculation of the area of irrigation bajayu obtained NPV = Rp.1.235.038.404.979,95-, IRR = 32% BCR = 6.92.And calculation of sensitivity analysis has also been done to change of cost and benefit equal to ± 5% and ± 10% for financial and economic analysis indicate that project plan still very feasible.